Hypotheses of development and strategies for overcoming drug resistance in epilepsy. Part I: Hypotheses of development - A. M. Yakimov; E. E. Timechko; A. I. Paramonova; A. A. Vasilieva; F. K. Rybachenko; A. D. Rybachenko; D. V. Dmitrenko (Эпилепсия и пароксизмальные состояния)
Currently, the problem of effective therapy for drug-resistant epilepsy remains vastly relevant. The severity of drug-resistant epilepsy, remarkable negative social sequelae and sudden death in epilepsy pose a heavy burden on healthcare system. Although many innovative antiepileptic drugs have been developed in recent decades, surgical approach remains the only effective way to treat drug-resistant epilepsy which is coupled to significant health risks and does not guarantee freedom from seizures. The stumbling block in managing this pathology is the lack of knowledge on pathogenetic mechanisms, leaving a significant proportion of patients without quality medical care. There are different viewpoints on developing drug resistance in epilepsy, which are characterized by multilayered and overlapping molecular disease bases. The review presents the analysis of the existing hypotheses regarding the mechanisms underlying drug resistance development in epilepsy.